Sustainable Energy Planning and Management with PV, Waste heat, positive energy districts and CO2 accounting - Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2024)
This 41st volume of the International Journal of Sustainable Energy Planning and Management includes three categories of papers: Ordinary submissions, submissions from the 2023 Smart Energy Systems Conference held in Copenhagen, Denmark and a submission from the 2023 Sustainable Development of Energy, Water and Environmental Systems (SDEWES) conference series. The work presented address photo voltaics (PV) in the arctic and in Sweden and electricity system scenarios of Indonesia based on, e.g. PV. Staying with PV a study investigated the interplay between PV and electric vehicles in Denmark. Moving to district heating, two papers address waste heat utilisation and positive energy districts respectively, and finally a study proves into unavoidable carbon dioxide emissions in Austria accounts for carbon capture and storage (CCS) and carbon capture and utilisation (CCUS) needs and possibilities.